Peran Generasi Muda dalam Membangun Perspektif Global yang Lebih Baik: Penelitian - Ardya Syaqibilla Nadine; Nabila Anastasya; Aulia Fitriana Adrian; Ifdah Aulia; Risdalina; Silvina Noviyanti (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
Amid global challenges such as climate change, social inequality, and the development of digital technology, the younger generation has a very strategic role in shaping a more inclusive, critical, and sustainable global perspective. This article aims to examine the contribution of the younger generation in building global awareness through education, utilization of digital media, and involvement in social activism. Using a qualitative approach based on literature studies, this study reveals that global education is able to instill cross-cultural values and social responsibility from an early age. On the other hand, digital literacy provides space for young people to become active actors in the dissemination of constructive global narratives. Their participation in various social movements also shows concern for humanitarian and environmental issues. However, challenges such as inequality in access to education, digital disinformation, and lack of participatory space are still obstacles. Therefore, synergy is needed between educational institutions, government, and society to create an ecosystem that supports the role of the younger generation as agents of global change.